Spin-crossover behaviors in solvated cobalt(ii) compounds1. Issue 20 (28th May 2015) - Hayami, Shinya; Nakaya, Manabu; Ohmagari, Hitomi; Alao, Amolegbe Saliu; Nakamura, Masaaki; Ohtani, Ryo; Yamaguchi, Ryotaro; Kuroda-Sowa, Takayoshi; Clegg, Jack K.
<x xml:space="preserve">Abstract</x> SCO cobalt(ii) compounds with the methoxy group have been synthesized, which exhibit unique magnetic behaviors, two-step SCO or reverse spin transition caused by structural transition.